Protein-Based Structures for Food Applications: From Macro to Nanoscale - Martins, Joana T.; Bourbon, Ana I.; Pinheiro, Ana C.; Fasolin, Luiz H.; Vicente, António A. (Frontiers in Sustainable Food Systems, 2018)
Abstract Novel food structures’ development through handling of macroscopic and microscopic properties of bio-based materials (e.g., size, shape and texture) is receiving a lot of attention since it allows controlling or changing structures’ functionality. Proteins are among the most abundant and employed biomaterials in food technology. They are excellent candidates for creating novel food structures due to their nutritional value, biodegradability, biocompatibility, generally recognized as safe status and molecular characteristics. Additionally, the exploitation of proteins’ gelation and aggregation properties can be used to encapsulate bioactive compounds inside their network and produce consistent delivery systems at macro-, micro- and nanoscale. Consequently, bioactive compounds which are exposed to harsh storage and processing conditions and digestion environment may be protected and their bioavailability could be enhanced. In this review, a range of functional and structural properties of proteins which can be explored to develop macro-, micro- and nanostructures with numerous promising food applications was discussed. Also, this review points out the relevance of scale on these structures’ properties, allowing appropriate tailoring of protein-based systems such as hydrogels and micro- or nanocapsules to be used as bioactive compounds delivery systems. Finally, the behaviour of these systems in the gastrointestinal tract and the impact on bioactive compound bioavailability are thoroughly discussed.